2017
DOI: 10.1002/glia.23207
|View full text |Cite
|
Sign up to set email alerts
|

ADAMTS‐4 in oligodendrocytes contributes to myelination with an impact on motor function

Abstract: Myelination is a late developmental process regulated by a set of inhibitory and stimulatory factors, including extracellular matrix components. Accordingly, chondroitin sulfate proteoglycans (CSPGs) act as negative regulators of myelination processes. A disintegrin and metalloproteinase with thrombospondin motifs type 4 (ADAMTS-4) is an extracellular protease capable of degrading CSPGs. Although exogenous ADAMTS-4 has been proven to be beneficial in several models of central nervous system (CNS) injuries, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 78 publications
(105 reference statements)
2
8
0
Order By: Relevance
“…In the adult mouse brain, expression of β-galactosidase was exclusively localized to Olig2-positive oligodendrocytes. Further studies demonstrated that ADAMTS4 expression was restricted to cells co-expressing adenomatous-polyposis-coli protein, a marker for mature oligodendrocytes [61]. Finally, the exclusive expression of ADAMTS4 in oligodendrocytes is consistent with our immunohistochemical detection of Aβ4-x peptides in white matter fiber tracts and neuronal processes in cortical areas.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…In the adult mouse brain, expression of β-galactosidase was exclusively localized to Olig2-positive oligodendrocytes. Further studies demonstrated that ADAMTS4 expression was restricted to cells co-expressing adenomatous-polyposis-coli protein, a marker for mature oligodendrocytes [61]. Finally, the exclusive expression of ADAMTS4 in oligodendrocytes is consistent with our immunohistochemical detection of Aβ4-x peptides in white matter fiber tracts and neuronal processes in cortical areas.…”
Section: Discussionsupporting
confidence: 85%
“…This was further confirmed in a proteome study of murine brain cell types, in which ADAMTS4 belonged to the 10 most abundant proteins specifically expressed in cultured murine oligodendrocytes [69]. Most importantly, during the preparation of this manuscript, another research group had reported the use of the same ADAMTS4 −/− KO reporter mouse strain to study the expression of ADAMTS4 in the brain, and had also detected ADAMTS4 in oligodendrocytes [61]. In the adult mouse brain, expression of β-galactosidase was exclusively localized to Olig2-positive oligodendrocytes.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Firstly in C0 (OLG), we found ADAMTS4, a protease that controls the degradation of a brain-specific extracellular matrix protein -brevican [102], specifically expressed in mouse cells (Figure 4f). Previously ADAMTS4 has been reported to be a marker of mature oligodendrocytes in mouse brain and may promote the generation of myelin sheath [103]. Additionally, TMEM125 and TSPAN2, both known to contribute to neuron myelination in mouse or rat [104,105], also displayed a similar expression pattern as ADAMTS4 ( Figure S7).…”
Section: Divergence Of Brain Functions In Pig and Mousementioning
confidence: 62%